Fencing as a Part of the Urban Context of the District Blasewitz in Dresden - Potapova, Anastasia (project baikal, 2013)
Every city has its unique urban context including the objects that form the historical environment of the city; the material elements represented by buildings, constructions, sculptural and architectural forms, elements of spatial surroundings of monuments and terraced houses; the atmosphere, the landscape elements, and the visage as an element expressing the real nature of the visual object, that is the city space (the open space “enclosed” by material elements).The city of Dresden is not an exception. In its district Blasewitz, one of the most important aspects of urban context is expressed by the fences of the Gründer Epoch. These pompous and fine constructions separating the street space from the park villas have remained since the middle of the XIX century.The article explores the origin of villas as an urban ensemble of the Italian architecture, the development of this type of architecture in the 18-19th centuries and the methods of preservation of all the elements of this structure, including fences. It describes the fences remained in the district Blasewitz and their unique features.
Keywords: Urban context; fencing; Gründer Epoch